EFFECTS OF ENVIRONMENTAL PARAMETERS ON PLANKTON ASSEMBLAGE IN AJIWA RESERVOIR, KATSINA STATE, NIGERIA - Suleiman, U. F.; Ibrahim, S.; Isyaku, H. I.; Nabila, T. I.; Amir, A.; Nadede, A. S.; Bello, L. (FUDMA JOURNAL OF SCIENCES, 2021)
The effect of environmental (Physicochemical) and biological (plankton) parameters of Ajiwa reservoir were studied for a period of eight months (March–October 2018). Field and laboratory activities were carried out using standard protocols. Mean monthly values of Temperature ranged between 25.87±3.57°C–29.46±0.66°C, Electrical conductivity was between 32.00±3.46µs/cm–210.00±95.39µs/cm. Dissolve Oxygen, Total Dissolved Solid and Biological Oxygen Demand Means of monthly values ranges between 5.53±0.39mg/l–9.35±0.62mg/l, 33.087±0.06mg/l–84.01±4.37mg/l, and 2.69±0.34mg/l–7.27±1.88mg/l. While phosphate and nitrate means of monthly values ranges between 0.04±0.02mg/l–0.09±0.03mg/l, 0.03±0.01mg/l–0.09±0.02mg/l. Four Phytoplankton phyla dominated by Chlorophyta (387org/L), Euglenophyta (160 org/L), Cyanophyta (83 org/L) and Bacillariophyta (63 org/L) were recorded in the reservoir. The Zooplanktons fauna comprises of Rotifers (180 org/L), Cladocerans (149 org/L) and Copepods (78 org/L). Correlation matrix showed that there were significant correlation between Phytoplankton, Zooplankton and Physicochemical parameters. The composition of planktons in the reservoir were affected by seasonal variations and fluctuation of physicochemical parameters
Keywords: Phytoplankton, Ajiwa, Reservoir, Physicochemical, Copepod